2023
DOI: 10.3390/cancers15102758
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of Resveratrol in Cancer Metastasis: From Biology to Therapy

Abstract: Cancer metastasis is a significant challenge in cancer treatment, and most existing drugs are designed to inhibit tumor growth but are often ineffective in treating metastatic cancer, which is the leading cause of cancer-related deaths. Resveratrol, a polyphenol found in grapes, berries, and peanuts, has shown potential in preclinical studies as an anticancer agent to suppress metastasis. However, despite positive results in preclinical studies, little progress has been made in clinical trials. To develop resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…Furthermore, the anti-cancer properties of RSV against colorectal cancer have been proven through many clinical trials. In one explanation, RSV acts as a chemosensitizer that modifies many subcellular pathways (p38-MAPK, Akt/STAT3, IL-6/JAK, and other signaling pathways) altering angiogenesis, apoptosis, metastasis, and transcription factors (RSV inhibits the NF-kB and its promoted end-proteins) suppressing cancer plasticity [ 59 , 60 ]. In lung cancer as well, signaling pathways involved in cancer progression such as the mTOR, PI3K/Akt, Wnt/B-catenin are targeted by RSV as a mechanism to reduce the cancer burden [ 61 ].…”
Section: Structure and Therapeutics Of Resveratrolmentioning
confidence: 99%
“…Furthermore, the anti-cancer properties of RSV against colorectal cancer have been proven through many clinical trials. In one explanation, RSV acts as a chemosensitizer that modifies many subcellular pathways (p38-MAPK, Akt/STAT3, IL-6/JAK, and other signaling pathways) altering angiogenesis, apoptosis, metastasis, and transcription factors (RSV inhibits the NF-kB and its promoted end-proteins) suppressing cancer plasticity [ 59 , 60 ]. In lung cancer as well, signaling pathways involved in cancer progression such as the mTOR, PI3K/Akt, Wnt/B-catenin are targeted by RSV as a mechanism to reduce the cancer burden [ 61 ].…”
Section: Structure and Therapeutics Of Resveratrolmentioning
confidence: 99%
“…The ability of resveratrol to specifically alter numerous important cellular pathways implicated in tumor progression is one of the reasons it has gained so much attention as an anti-cancer agent with multiple applications [67][68][69][70][71]. A vast number of studies revealed the chemopreventive effect of resveratrol in various experimentally induced tumor models, such as skin, lung, gastric, colon, liver, pancreas, prostate, bladder, breast, ovarian, esophagus, thyroid, etc.…”
Section: Mechanisms Of Resveratrol In Cancer Preventionmentioning
confidence: 99%
“…A vast number of studies revealed the chemopreventive effect of resveratrol in various experimentally induced tumor models, such as skin, lung, gastric, colon, liver, pancreas, prostate, bladder, breast, ovarian, esophagus, thyroid, etc. [67][68][69][70][71]. Resveratrol exposure induced differentiation in canine oral mucosal melanoma cells, enhancing their sensitivity to cisplatin and increasing the mRNA expression of melanoma differentiation markers, such as microphthalmia-associated transcription factor (MITF) [72].…”
Section: Mechanisms Of Resveratrol In Cancer Preventionmentioning
confidence: 99%
See 2 more Smart Citations